The Contribution of Local Wisdom in the Green Governance Framework in Bromo Tengger Semeru National Park - Wishnu Mahendra Wiswayana; Primadiana Yunita; Firstyarinda Valentina Indraswari; Ella Joy Avellanoza Ponce (Journal of Innovation in Educational and Cultural Research, 2024)
Taman Nasional Bromo Tengger Semeru (TNBTS), home to the Tengger Tribe, is being developed by the government to become a major tourist destination as a part of the "10 New Bali" initiative. However, despite its national park status and the government's ambitious initiative, TNBTS faces significant environmental problems like non-protected areas. Therefore, this research aims to examine how local wisdom practices confront environmental challenges and governance issues within TNBTS. Utilizing a qualitative descriptive method, the study relies on secondary data from reports, academic journals, and other relevant publications. The findings reveal that local wisdom significantly contributes to sustainable environmental management, demonstrating resilience and adaptability amidst modern pressures. This research contributes to the scientific understanding of how local wisdom can inform and improve environmental governance, highlighting its crucial role in addressing ecological challenges in the context of globalization. The study concludes that integrating indigenous practices with contemporary governance can enhance environmental sustainability in TNBTS.